Development of Sustainable Minapolitan Area in Tamako District, Kepulauan Sangihe Regency - Sahaduta, Yegar; Kalampung, Hebzibah; Koswara, Arwi Yudhi (Syntax Literate, 2024)
The aim of this study is to address the challenges facing the Dagho Beach Fishing Port Area in North Sulawesi, which plays a pivotal role in the region's fisheries sector but suffers from inefficiencies in development systems, markets, distribution, and infrastructure. This dependence on natural resources has eroded community independence, exacerbated by issues such as illegal fisheries transactions, price disparities, and the absence of processing industries. Additionally, limited accessibility for exports and regulatory hurdles impede the area's potential, with only a small fraction of the population engaged in fishing activities. To tackle these issues, the study employs a comprehensive four-stage analysis approach. Firstly, Descriptive Analysis delineates the economic, political, social, and environmental characteristics of the area. Secondly, Analytical Hierarchy Processes (AHP) identify the most influential indicators for focused development efforts. Thirdly, a combination of Scalogram and Weighted Sum methods determines suitable minapolitan zones. Finally, Descriptive Direction offers development guidelines based on previous analyses. The research yields actionable directions, including the establishment of a modern market, enhancing fishery product marketing through the "Marketing Mix" and Free Trade Agreement (FTA) implementation. It advocates for technology-based processing units and integrated infrastructure, alongside policy development to support the fisheries industry and promote sustainable practices. The study emphasizes the importance of infrastructure development, economic collaboration, and community empowerment initiatives to foster local fishery development, cultivation, and business capital.